Characterization of Cutinase - Chen, Sheng (Cutinase: Preparation and Application, 2021)
In previous work, T. fusca cutinases (Tfu_0883 and Tfu_0882) have been isolated and identified, with 93% similarity in amino acid sequence. Biochemical characteristics of T. fusca cutinases were investigated for the first time. F. solani pisi cutinase was used as a control for a better comparison of cutinases from bacterium and fungi. This study has shown that T. fusca cutinases as monomeric proteins exhibited a broad substrate specificity, which could hydrolyze plant cutin, insoluble triglycerides, and soluble esters. T. fusca and F. solani pisi cutinase are similar in substrate kinetics without interfacial activation. T. fusca cutinases showed higher thermal stability in the presence of surfactants and organic solvents, which might have promising applications in related industries.